COVID-19 impacts on cross-border mobility of senior population between Shenzhen and Hong Kong - He, Shi; Niu, Caicheng; Wei, Yue; Cai, Yinger; Zhang, Wen; Xiao, Yingbo; Yin, Jie (Frontiers in Public Health, 2023)
The onset of the COVID-19 outbreak led to widespread adoption of mobility intervention policies, which were widely regarded as effective measures to control the spread of the virus. The initial pandemic wave, accompanied by the enforcement of mobility intervention policies, greatly changed human mobility patterns, especially cross-border mobility (CBM). This study investigates the impact of the first wave of the pandemic and related mobility intervention policies on the CBM of the senior population between Shenzhen and Hong Kong. Based on anonymous mobile phone trajectory data from 17 million devices active in Shenzhen spanning December 2019 to May 2020, we consider the implementation of four stages of mobility intervention policies in both cities. We adopt interrupted time series analysis to explore the causal effects of different mobility intervention policies on the CBM of older people between Hong Kong and Shenzhen. We find that most mobility intervention policies have a significant abrupt or gradual effect on the CBM of older people, especially in the 60-64 age group. As these policies neglect the mobility needs and characteristics of among the senior groupsolder people in different age groups, such as visiting relatives or friends and seeking medical treatment across borders, we suggest that more coordinated and integrated policies and measures are required to address the CBM needs of older people in Shenzhen and Hong Kong, especially in the post-pandemic era.